Difficulties in Learning English Faced By Visually Impaired Students at Center of Language Development (P2B) in State Islamic University (UIN) Sunan Kalijaga - Aryanti, Widya (PLD UIN Sunan Kalijaga, 2014)
The objectives of this research are to describe some learning strategies and difficulties faced by visually impaired students (VIS) in learning English at UIN Sunan Kalijaga and to describe some strategies of the lecturer in dealing with difficulties in English teaching and learning process for VIS at UIN Sunan Kalijaga.The type of research is descriptive qualitative research in the form of case study. In this research, the researcher used two instruments. They are observation and interview. There are three subjects involved in this research. They are two blind students and one low vision students. The observation was done when the researcher did teaching and learning process at Class Dakwah R. The data were taken from observation and interview. The researcher used the data to analyze the VIS’ difficulties in learning English.The result shows that there are some difficulties faced by VIS. These difficulties can be put into two different categories: internal and external difficulties. Internal difficulties come from the VIS themselves which relates to VIS’ sight conditions and their learning strategies. External difficulties come from the learning environment including difficulties from the lecturer, friends, materials and the facilities.VIS have different learning strategies. The lecturer should discuss some classroom adaptations such as seating arrangement, friends’ assistance and peer teaching, adapted facilities and exam accommodation, for instance exam assistance, longer exam time, inclusive examination and larger print for low vision students. Finally, the lecturer should choose appropriate teaching strategies, media and teaching aids.